Who Is Conducting "Better" Employment Interviews? Antecedents of Structured Interview Components Use - Roulin, Nicolas; Bourdage, Joshua; Wingate, Timothy (Personnel Assessment and Decisions, 2019)
The employment interview remains a unique paradox. One the one hand, decades of research demonstrates that using more structured components (e.g., question consistency, evaluation standardization) can largely improve the psychometric properties of interviews. On the other hand, although interviews are almost universally used, many interviewers still resist using structured formats. We examined the use of seven structure components by 131 professional interviewers, and their association with three types of antecedents: interviewers’ background (e.g., experience, training), the focus of the interview (selection vs. recruitment), and interviewers’ personality (based on the HEXACO model). Interviewers’ background (i.e., training) and the focus of the interview were largely associated with the use of question sophistication, question consistency, note-taking, or evaluation standardization. Personality (i.e., extraversion) was mostly associated with rapport-building or probing. Our findings highlight the importance of providing formal training to interviewers, but suggest that attempting to eliminate less-structured components could encounter resistance from some interviewers.